The determinants of fund performance: does size really matter in South Africa? - Ramos, D. (My University, 2018)
This research seeks to better understand the determinants of fund performance in a South African context. It will focus extensively on fund size, past performance, fees, and expense ratios and their relationship with performance. While other research has shown an inverse relationship between fees and performance, it seems divided on the relationship between fund size and performance in various markets. Due to the high regulatory environment, asset managers in South Africa face multiple restrictions that have limited their investible universe. The results presented in this research show that funds in South Africa exhibit the “Hot Hands” phenomenon as well as it documents the negative relationship between fees and performance for South African funds. Lastly, results show a positive relationship between fund size and performance where funds in South Africa enjoy economies of scale.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Commerce (M .Com (Finance) in the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2018
Keywords: Johannesburg Stock Exchange; Stocks--Prices--South Africa; Capital market--South Africa